1998
DOI: 10.1046/j.1365-2133.1998.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

The intradermal effects of the H3 receptor agonist R α methylhistamine in human skin

Abstract: We have investigated the possible existence of the H3 histamine receptor in human skin with the highly selective ligands R alpha methylhistamine (RAMHA) (H3 agonist) and thioperamide (H3 antagonist). We compared the intradermal effects of RAMHA with histamine, and studied their potential modulation by the H1 antagonist terfenadine, and H2 antagonist cimetidine. The effects of RAMHA and thioperamide on codeine phosphate-, substance P- and histamine-induced weal and flare responses were also studied. RAMHA produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…These investigators concluded that H 3 receptors do not appear to inhibit histamine release in human skin. Consistent with the observations of Kavannagh et al (1998) we presently show that thioperamide or clobenpropit given alone at doses that block H 3 receptors in vivo does not alter the cutaneous microvascular permeability responses elicited by compound 48/80 (McLeod et al, 1996(McLeod et al, , 1999. However, when histamine H 1 receptors were blocked with chlorpheniramine, we demonstrate a significant H 3 component contributing to the extravasation of Evans blue evoked by compound 48/80.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These investigators concluded that H 3 receptors do not appear to inhibit histamine release in human skin. Consistent with the observations of Kavannagh et al (1998) we presently show that thioperamide or clobenpropit given alone at doses that block H 3 receptors in vivo does not alter the cutaneous microvascular permeability responses elicited by compound 48/80 (McLeod et al, 1996(McLeod et al, , 1999. However, when histamine H 1 receptors were blocked with chlorpheniramine, we demonstrate a significant H 3 component contributing to the extravasation of Evans blue evoked by compound 48/80.…”
Section: Discussionsupporting
confidence: 92%
“…Kavannagh et al (1998) showed that i.d. Ra-methylhistamine, an H 3 agonist, produces wheal and flare responses in human skin.…”
Section: Discussionmentioning
confidence: 98%
“…6 Recently described histamine H3 receptors behave as autoreceptors regulating release and biosynthesis of histamine in the central nerous system (CNS) and other tissues, including skin. 7,8 The H3 receptors may also form a link with other receptor systems, making the whole picture even more confusing. 9 The majority of histamine released in the skin originates from the dermal mast cells.…”
Section: Peripheral Itching Mediators Histaminementioning
confidence: 99%
“…The existence and the role of the histamine H 3 receptor in skin is still unclear in humans 22 . However, in rats, the histamine H 3 receptor on mast cells is involved in the inhibitory effect on histamine release, 23 and the regulation of substance P release is also mediated via prejunctional histamine H 3 receptors located on peripheral endings of sensory nerves 24 .…”
mentioning
confidence: 99%